Kombucha Versus Vegetal Cellulose for Affordable Mucoadhesive (nano)Formulations - Ioana Popa-Tudor; Naomi Tritean; Ștefan-Ovidiu Dima; Bogdan Trică; Marius Ghiurea; Anisoara Cimpean; Florin Oancea; Diana Constantinescu-Aruxandei (Gels, 2025)
Cellulose nanofibers gained increasing interest in the production of medical devices such as mucoadhesive nanohydrogels due to their ability to retain moisture (high hydrophilicity), flexibility, superior porosity and durability, biodegradability, non-toxicity, and biocompatibility. In this work, we aimed to compare the suitability of selected bacterial and vegetal nanocellulose to form hydrogels for biomedical applications. The vegetal and bacterial cellulose nanofibers were synthesized from brewer’s spent grains (BSG) and kombucha membranes, respectively. Two hydrogels were prepared, one based on the vegetal and the other based on the bacterial cellulose nanofibers (VNC and BNC, respectively). VNC was less opaque and more fluid than BNC. The cytocompatibility and in vitro antioxidant activity of the nanocellulose-based hydrogels were investigated using human gingival fibroblasts (HGF-1, ATCC CRL-2014). The investigation of the hydrogel–mucin interaction revealed that the BNC hydrogel had an approx. 2× higher mucin binding efficiency than the VNC hydrogel at a hydrogel/mucin ratio (mg/mg) = 4. The BNC hydrogel exhibited the highest potential to increase the number of metabolically active viable cells (107.60 ± 0.98% of cytotoxicity negative control) among all culture conditions. VNC reduced the amount of reactive oxygen species (ROS) by about 23% (105.5 ± 2.2% of C−) in comparison with the positive control, whereas the ROS level was slightly higher (120.2 ± 3.9% of C−) following the BNC hydrogel treatment. Neither of the two hydrogels showed antibacterial activity when assessed by the diffusion method. The data suggest that the BNC hydrogel based on nanocellulose from kombucha fermentation could be a better candidate for cytocompatible and mucoadhesive nanoformulations than the VNC hydrogel based on nanocellulose from brewer’s spent grains. The antioxidant and antibacterial activity of BNC and both BNC and VNC, respectively, should be improved.